Lack of mitochondrial DNA structure in Balkan donkey is consistent with a quick spread of the species after domestication. (27th August 2013) - Pérez‐Pardal, L.; Grizelj, J.; Traoré, A.; Cubric‐Curik, V.; Arsenos, G.; Dovenski, T.; Marković, B.; Fernández, I.; Cuervo, M.; Álvarez, I.; Beja‐Pereira, A.; Curik, I.; et al.
Summary A total of 132 mtDNA sequences from 10 Balkan donkey populations were analysed to ascertain their regional genetic structure and to contribute to the knowledge of the spreading of the species after domestication. The Balkan donkey sequences were compared with those from 40 Burkina Faso donkeys as an African outgroup to account for possible local Balkan scenarios. The 172 sequences gave 62 different haplotypes (55 in Balkan donkey). Virtually all the analysed populations had haplotypes assigned to either Clade 1 or Clade 2 even though the relative proportion of Clade 1 or 2 haplotypes differed across populations. Geographical maps constructed using factors computed via principal component analysis showed that the Balkan donkey populations are not spatially structured. AMOVA confirmed a lack of genetic structure in Balkan donkey mtDNA. Balkan populations were poorly differentiated (ΦST = 0.071). Differentiation between the Balkan donkey and the African outgroup also was low. The lack of correspondence between geographical areas and maternal genetic structure is consistent with the hypothesis suggesting a very quick spread of the species after domestication. The current research illustrates the difficulties to trace routes of expansion in donkey, as the species has no geographical structure.